Pengaruh Komunikasi Terhadap Produktivitas Kerja di Moderating Komitmen Pegawai di Bank Sumsel Babel Cabang Lubuklinggau - Hardi Mulyono; Irma Idayati; Suyadi Suyadi (Forum Kerjasama Pendidikan Tinggi (FKPT), 2022)
The problem in this study is the effect of communication on work productivity in moderating employee commitment at Bank Sumsel Babel Lubuklinggau Branch. This study uses observation data collection methods, distributing questionnaires, and conducting documentation to find data. This study shows that communication has a significant effect on work productivity in moderating employee commitment. The results of this study indicate that communication partially has an influence on work productivity with an R square value of 0.389 or 38.9% and employee commitment as a moderating variable strengthens the relationship between communication and work productivity with an R square value of 0.456 or 45.6%. It can be concluded that communication affects work productivity at Bank Sumsel Babel Lubuklinggau Branch, further after being moderated by employee commitment, resulted in a significant increase in work productivity.